2010
DOI: 10.1261/rna.2379610
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic isomiR regulation in Drosophila development

Abstract: Several recent reports have demonstrated that microRNAs (miRNAs) can exhibit heterogeneous ends and post-transcriptional nontemplate 39 end additions of uridines or adenosines. Using two small RNA deep-sequencing data sets, we show here that these miRNA isoforms (isomiRs) are differentially expressed across Drosophila melanogaster development and tissues. Specifically, we demonstrate that: (1) nontemplate nucleotide additions of adenosines to miRNA 39 ends are highly abundant in early development; (2) a subset… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

16
174
1
4

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 195 publications
(195 citation statements)
references
References 41 publications
16
174
1
4
Order By: Relevance
“…A full description of individual sample characteristics and small RNA annotation data are provided in SI Appendix, Table S1. Median total RNA recovery was 18 ng/mL of maternal plasma [interquartile range (IQR) [14][15][16][17][18][19][20], 45 ng/mL of fetal plasma (IQR 34-91), 15 ng/mL of paternal plasma (IQR 13-18), and 23 ng/mL in nonpregnant women's sera or plasma . Two fetal plasma samples had outlying RNA content; 500 and 1,250 ng/mL, possibly explained by cell lysis and release of RNA from the placenta or collection of umbilical cord blood close to the placenta resulting in capture of plasma containing a higher concentration of RNA.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A full description of individual sample characteristics and small RNA annotation data are provided in SI Appendix, Table S1. Median total RNA recovery was 18 ng/mL of maternal plasma [interquartile range (IQR) [14][15][16][17][18][19][20], 45 ng/mL of fetal plasma (IQR 34-91), 15 ng/mL of paternal plasma (IQR 13-18), and 23 ng/mL in nonpregnant women's sera or plasma . Two fetal plasma samples had outlying RNA content; 500 and 1,250 ng/mL, possibly explained by cell lysis and release of RNA from the placenta or collection of umbilical cord blood close to the placenta resulting in capture of plasma containing a higher concentration of RNA.…”
Section: Resultsmentioning
confidence: 99%
“…Changes in the relative distribution of isomiRs have been found in different developmental and disease states. For example, nontemplate additions of adenosines to the 3′ ends of miRNAs are highly abundant early in Drosophila development (18); some isomiRs preferentially occur in benign gastric tissue, whereas other isomiRs preferentially occur in gastric tumors (19).…”
mentioning
confidence: 99%
“…Data from large-scale screens indicated the expression of miR-282 in pupae and female adults and a low-level maternal contribution in the embryos (Lai et al 2003;Leaman et al 2005;Fernandez-Valverde et al 2010). According to miRBase, the predicted mir-282 pre-miRNA is 97 nt long and gives rise to a single miRNA of 28 nt (Griffiths-Jones et al 2008); however, deep sequencing data indicate a shorter miR-282 of 22 nt with additional nontemplate adenosine nucleotides at the 39 end (Fernandez-Valverde et al 2010;Kozomara and Griffiths-Jones 2011).…”
Section: Molecular Definition Of the Mir-282 Genementioning
confidence: 99%
“…Besides leading to a new appreciation of miRNA*, next generation sequencing (NGS) studies have further identified start and end site variants of many known miRNAs, termed isomiRs (26,30,31) (Fig. 1B).…”
Section: Mirna Processing Variantsmentioning
confidence: 99%
“…They can arise through altered Drosha and Dicer cleavage as well as trimming and nontemplated addition of the 3 0 end postprocessing (35-38). It is likely that 3 0 end variation is also biologically important, as it can be developmentally regulated (30) and there is evidence that it can alter miRNA turnover (39), and loading into one of the four mammalian AGO proteins (23). Although 3 0 isomiRs share a common seed sequence, 3 0 end changes can impact target selection or efficiency of repression in some cases.…”
Section: Mirna Processing Variantsmentioning
confidence: 99%